2012
DOI: 10.5588/ijtld.11.0522
|View full text |Cite
|
Sign up to set email alerts
|

First- and second-line anti-tuberculosis drug resistance in Northwest Ethiopia

Abstract: A substantial number of new and previously treated cases harbour MDR-TB. We recommend DST at least for previously treated cases, patients who remain smear-positive at the end of the second month of treatment and patients in close contact with MDR-TB cases. Improved infection control measures need to be implemented in Ethiopia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
52
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(72 citation statements)
references
References 0 publications
15
52
5
Order By: Relevance
“…Similar results were reported in other studies [22, 23, 39]. Whereas other studies from different parts of Ethiopia showed lack of association between HIV infection and drug resistance [19, 21, 40]. …”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Similar results were reported in other studies [22, 23, 39]. Whereas other studies from different parts of Ethiopia showed lack of association between HIV infection and drug resistance [19, 21, 40]. …”
Section: Discussionsupporting
confidence: 90%
“…This is relatively higher than previous reports from other parts of Ethiopia, such as Jimma (18.4%) [19], Arsi, (18.2%) [20], and Gondar (10.7%) [21]. A comparable rate of resistance (21%) [22] was reported from Addis Ababa, whereas higher rates of resistance (32.5%) [3], (30.1%) [23], and (25%) [24] have also been reported from similar surveys in the country in the previous years.…”
Section: Discussioncontrasting
confidence: 60%
See 2 more Smart Citations
“…It is a fully automated diagnostic molecular test using real-time polymerase chain reaction (PCR) technology to simultaneously detect M. tuberculosis and rifampicin resistance mutations in the rpoB gene [13]. The Xpert assay is highly rapid, sensitive and specific in diagnosis of both pulmonary and extra pulmonary TB [814]. Furthermore; it was shown to be cost-effective for TB diagnosis compared to microscopy in low and middle income settings [14].…”
Section: Introductionmentioning
confidence: 99%